Analisa Pengaruh Faktor Penarik, Faktor Eksternal dan Faktor Travel Stimuli Dalam Pengambilan Keputusan Pembelian Paket Wisata ke Vietnam oleh Wisatawan Surabaya - Novilia Rosana (Tourism Retailing+, 2013)
This study was conducted to assess the influence of pull factors, external factors and stimuli travel factor in the purchase decision making Vietnam tour packages to tourists Surabaya and the most decisive factor in the pull factors, external factor, stimuli travel factor in purchasing travel packages to Vietnam in Surabaya . The variables in this study is the location climate, expenditure or prices, close to another destination, advertising, travel pictures and the reference group. Analysis techniques that used in this study is the multiple linear regression, F test, t test, as well as cross-tabulation analysis. The results showed that the variable characteristics of the destination or pull factors of tourist destinations are the dominant influence on purchasing decisions Vietnam tour packages in Surabaya.